Pengaruh Pembebanan Terhadap Nilai Resistansi Pentanahan Pada Transformator 250 KVA Gardu BA 0005 PT. PLN (Persero) UP3 Bengkulu ULP Teluk Segara Bengkulu - Putra, Dian Eka; Idris, Iswadi (UNIVERSITAS MUHAMMADIYAH PALEMBANG, 2020)
The distribution transformer is an electromagnetic device that converts and transfers electrical energy to the primary and secondary electrical distribution networks, which are directly related to the ever changing load center. As a result of high and unbalanced loading, it will cause an increase in current in neutral, of course, to anticipate changes in the load that cause a neutral phase current in the distribution transformer, a low grounding resistance value is required in the neutral phase.The resistance value or grounding resistance according to PUIL 2000 and SPLN3-1978 Regarding PLN Low Voltage Network Grounding and Installation Grounding does not exceed 5 ? or a maximum of 5 ?. The calculation results obtained that the grounding resistance value in the neutral phase and the transformer body 250 KVA Distribution Substation BA 005 is 4.11 ?. From these results there is a need for a comparative study of the resistance value from the calculation results with the value of the direct measurement results in the neutral phase grounding system and the 250 KVA transformer body BA 005 Distribution Substation. From the results of direct measurements between 14.00 to 15.00 WIB with 50 percent loading on The transformer has the largest value of resistance in the neutral phase of 8.1 ? and on the transformer body of 8.3 ?. Then the increase in the value of the neutral grounding resistance and the grounding resistance of the transformer body 250 KVA is caused by the transformer load factor and weather factors, especially in sunny and hot weather.